G61(P) Improving the sexual health of homelessyoung people. (24th May 2017) - McGregor, F; Robinson, A; Shawe, J
Abstract : Aims: The study examined knowledge and attitudes around Sexual Health (SH) and contraceptive use among Young People (YP) who are homelessness and resident in hostels in a large urban area and their key workers. The aim was to improve SH outcomes through building a model of SH care appropriate to the needs of YP. Less is known about SH in homeless young males' than females', thus the study aimed to ensure inclusion of male views. Methods: A constructivist theoretical framework was used to underpin this qualitative ethnographic case study. The case under study being homeless YP, girls, boys or transgender, aged 16–21 years resident in homeless hostel accommodation. Participants were selected by purposive sampling in order to ensure maximum variety within the case. Twenty-nine homeless YP, and five key workers were recruited from homeless hostels and a homeless day-centre in a large urban area. One to one semi-structured interviews were carried out examining knowledge and attitudes concerning SH and contraceptive use. Insider observations of resident's meetings and the hostel and centre settings were undertaken. A reflexive approach was used in interviewing. Demographic data was collected from YP participants. Nvivo 10 QSR computer assisted software was used to analyse the data thematically, and demographic data used to stratify and identify trends between males, females and age groups. Results: Four overarching themes were identified: Meaning of sexual health: ○ Tended to differ between males and females ○ Females made associations with emotions, relationships and safety ○ Males with using protection ○ Life experiences have overriding effect on: ○ Attitudes ○ Sexual well-being. ○ Being homeless poses risks and influences priority of SH: ○ Hygiene ○ Dangers ○ Survival ○ Use of SH services: ○ Barriers ○ Stigma and embarrassment ○ Staff attitudes Facilitators Using non SH services e.g. GPs Conclusion: Homeless YP resident in hostel accommodation require specialised delivery of SH care which is holistic and supports their needs. This could be provided within the familiar hostel or day-centre environment. It should be managed in a way that ensures facilitation of quality therapeutic relationships, with highly skilled workers, and sensitive dissemination of targeted information.